OPTIMALCARE: Community-based home care policy innovation in accelerating stunting reduction in Makassar City - Suprapto Suprapto; Darmi Arda; Maria Kurni Menga; Adji Saktiawan; Siprianus Nggaá Woge (LPPM Politeknik Sandi Karsa, 2025)
Stunting remains a significant public health challenge in Makassar City, with prevalence rates exceeding national targets and World Health Organization thresholds. Contributing factors include socioeconomic disparities, limited access to healthcare, suboptimal parenting practices, and inadequate nutritional intake. The OPTIMALCARE program introduces a community-based home care policy innovation to accelerate stunting reduction through integrated health services, family-centred nutrition education, routine growth monitoring, and a mobile nutrition monitoring application. This program engages health workers, Posyandu cadres, and community leaders to deliver proactive home visits, promote behavioral change, and ensure timely interventions. A participatory approach strengthens local capacity, fosters cross-sector collaboration, and leverages technology for real-time data collection and analysis. The initiative aligns with Sustainable Development Goals (SDG 2, SDG 3, and SDG 17), regional development priorities, and national research agendas on child health and nutrition. Through targeted outreach, community empowerment, and evidence-based interventions, OPTIMALCARE aims to improve healthcare accessibility, enhance parental knowledge, and foster sustainable community involvement, ultimately contributing to a significant decline in stunting prevalence in Makassar City